Biomechanical effects of digitally constructed titanium, modified polyetheretherketone, and polyetherketoneketone subperiosteal implants on atrophied maxilla: a finite element analysis - Mohammed A. El-Sawy; Basin El-Khatib; Hesham S. Borg; Mohamed T. Khater (BMC Oral Health)
Abstract Aim This study aimed to evaluate how different combinations of subperiosteal and superstructure framework materials—titanium, modified PEEK, and PEKK—affect stress distribution on bone in atrophic maxillae, using finite element analysis (FEA). Methods A three-dimensional finite element model of an atrophic maxilla was created from CT data and processed through CAD and ANSYS software. Nine combinations of framework materials were tested under three loading protocols (vertical, oblique, and incisor-directed forces). The subperiosteal framework was fixed in place by 12 mini-screw with different lengths, that the 3 materials were assigned to frameworks in 9 different combinations for the lowest stresses on bone. Three different loading protocols were applied to the prosthetic structure with each of frameworks materials combination. Results Titanium subperiosteal frameworks transferred the least stress to underlying bone and fixation screws, while modified PEEK and PEKK showed higher stress values, particularly under incisor loading. Titanium superstructures exhibited higher internal stresses due to rigidity but protected supporting structures more effectively. Cases under vertical incisors forces showed very high stress levels on cement layer and subperiosteal frame due to bending, and high stresses on mini-screws and bone. These levels were critical for cement layer, modified PEEK, and PEKK framework materials, bone, except, mini screws, that stresses level were in the safe region. Conclusion Within the limitations of this FEA analysis, Titanium is the optimal material for subperiosteal frameworks in atrophic maxillae due to its superior stress distribution. PEKK and modified PEEK may be viable alternatives in patients with reduced functional loading. Clinical significance Titanium subperiosteal framework should be considered the optimum material for subperiosteal implants. Modified PEEK and PEKK material can be considered as alternative material to titanium subperiosteal framework for patients with lower masticatory forces (complete denture on the opposite arch or on the anterior segment). Clinical trial registry number Registered at www.clinicaltrials.gov (NCT06362057) (2024-04-8).